Agroenvironmental transformation in the Sahel: Another kind of "Green Revolution" - Reij, Chris; Tappan, Gary; Smale, Melinda (International Food Policy Research Institute, 2009)
A farmer-managed, agroenvironmental transformation has occurred over the past three decades in the West African Sahel, enabling both land rehabilitation and agricultural intensification to support a dense and growing population. This paper traces the technical and institutional innovations, their impacts, and lessons learned from two successful examples. The first is the story of the improvement and replication of indigenous soil and water conservation practices across the Central Plateau of Burkina Faso. Rehabilitation of at least 200,000 hectares of degraded land enabled farmers to grow cereals on land that had been barren and intensify production through developing agroforestry systems. Additionally, rehabilitation appears to have recharged local wells. The second example is a farmer-managed process of natural regeneration, using improved, local agroforestry practices over an estimated 5 million hectares in southern Niger. This large-scale effort reduced wind erosion and increased the production and marketing of crops, fodder, firewood, fruit, and other products. In both cases, income opportunities were created, reducing incentives for migration. Women benefited from the improved supply of water, fuelwood, and other tree products. Human, social, and political capital was strengthened in a process of farmer-driven change. Fluid coalitions of actors expanded the scale of the transformation. These stories have important lessons for those who seek to create effective agricultural development partnerships and meet the challenges of climate change and food security.